The Online Education Impact on Students During Covid- 19 Pandemic - Saurabh Phanse (Universitas Pendidikan Indonesia, 2021)
The purpose of the study was to identify how online education impact students during the Covid-19 Pandemic, and to find the advantages and disadvantages of online education. This paper is also focused on changes in conducting exams and exam patterns. The data was taken from journals and my prior knowledge. Qualitative and quantitative methods were used for this research. The reason behind the study is the research paper show how online education impact on students and changes in teaching method and changes in exam patterns. This study also considered: (i) Why online education is mostly used? (ii) What advantages and disadvantages of online education? and (iii) How exams are conducted? The questionnaires were prepaid and circulated among students through email and WhatsApp. The result of the study shows the merits and demerits of online education. The mode of conducting exams also changes and some exams are also postponed. The effect of Covid-19 was very fast so it is very risky to conduct offline classes and therefore there is a change in teaching method. This article aims to provide a report on the impact of online education on students during a pandemic. Impact this study is important for the government, students, and teachers.